Vitamin B12 in Leber hereditary optic neuropathy mutation carriers: a prospective cohort study - Julia Zibold; Bettina von Livonius; Hana Kolarova; Günter Rudolph; Claudia S. Priglinger; Thomas Klopstock; Claudia B. Catarino (Orphanet Journal of Rare Diseases, 2022)
Abstract Background Leber hereditary optic neuropathy (LHON) is the most common mitochondrial disorder, frequently resulting in acute or subacute severe bilateral central vision loss. Vitamin B12 deficiency is also a known cause of optic neuropathy through mitochondrial dysfunction. Here we evaluated the prevalence and clinical significance of vitamin B12 deficiency in a large cohort of LHON patients and asymptomatic mutation carriers from a tertiary referral center. Methods From the Munich LHON prospective cohort study, participants included all LHON patients and asymptomatic LHON mutation carriers, who were recruited between February 2014 and March 2020 and consented to participate. Neurological, general, and ophthalmological examinations were regularly performed, as were laboratory tests. Vitamin B12 deficiency was diagnosed if serum vitamin B12 was below 201 pg/mL, or if 201–339 pg/mL plus low serum holotranscobalamin or elevated serum methylmalonic acid or elevated total plasma homocysteine. Results We analyzed 244 subjects, including 147 symptomatic LHON patients (74% males) and 97 asymptomatic mutation carriers (31% males). Median age at study baseline was 34 years (range 5–82 years). The prevalence of vitamin B12 deficiency was higher for LHON mutation carriers than for the general population in all age categories. This was statistically significant for the LHON mutation carriers under 65 years (21% vs. 5–7%, p = 0.002). While vitamin B12 deficiency prevalence was not statistically different between LHON patients and asymptomatic mutation carriers, its clinical correlates, e.g., macrocytosis and polyneuropathy, were more frequent in the subgroup of LHON patients. Excessive alcohol consumption was a significant predictor of vitamin B12 deficiency (p < 0.05). Conclusions The high prevalence of vitamin B12 deficiency in LHON mutation carriers, both asymptomatic mutation carriers and LHON patients, highlights the need for regular vitamin B12 screening in this population, in order to ensure early treatment, aiming for better outcomes. Our study is not conclusive regarding vitamin B12 deficiency as determinant for disease conversion in LHON, and further research is warranted to disentangle the role of vitamin B12 in the pathophysiology and prognosis of LHON.